2017
DOI: 10.1038/s41514-017-0016-9
|View full text |Cite|
|
Sign up to set email alerts
|

Repeat dose NRPT (nicotinamide riboside and pterostilbene) increases NAD+ levels in humans safely and sustainably: a randomized, double-blind, placebo-controlled study

Abstract: NRPT is a combination of nicotinamide riboside (NR), a nicotinamide adenine dinucleotide (NAD+) precursor vitamin found in milk, and pterostilbene (PT), a polyphenol found in blueberries. Here, we report this first-in-humans clinical trial designed to assess the safety and efficacy of a repeat dose of NRPT (commercially known as Basis). NRPT was evaluated in a randomized, double-blind, and placebo-controlled study in a population of 120 healthy adults between the ages of 60 and 80 years. The study consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
125
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(130 citation statements)
references
References 34 publications
4
125
0
1
Order By: Relevance
“…After supplementation with NAD + precursors, multiple beneficial effects have been observed, including improved mitochondrial health, increased muscle strength, and motor function . NAD + supplementation is being tested for various conditions (http://clinicaltrial.gov) and in studies so far, no side effects have been reported .…”
Section: The Effects Of Nad+ Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…After supplementation with NAD + precursors, multiple beneficial effects have been observed, including improved mitochondrial health, increased muscle strength, and motor function . NAD + supplementation is being tested for various conditions (http://clinicaltrial.gov) and in studies so far, no side effects have been reported .…”
Section: The Effects Of Nad+ Supplementationmentioning
confidence: 99%
“…After supplementation with NAD + precursors, multiple beneficial effects have been observed, including improved mitochondrial health, increased muscle strength, and motor function [107,148,150,161]. NAD + supplementation is being tested for various conditions (clinical trial.gov) and in studies so far, no side effects have been reported [159,162]. NAD + is required for efficient DNA repair as it promotes the activities of PARP1, RecQ helicases, sirtuins, and many other DNA repair enzymes, and DNA repair accessory factors [25].…”
Section: The Effects Of Nad + Supplementationmentioning
confidence: 99%
“…Dietary supplementation of NR in rodents increases NAD + levels in skeletal muscle (Canto et al 2012), and improves skeletal muscle and muscle stem cell function in mice with aging or muscular dystrophy Zhang et al 2016). The potential effects of NR in human skeletal muscle are unknown, but dietary supplementation of NR in humans increases NAD + and NAD + -related metabolites in plasma, peripheral blood mononuclear cells, and urine Dellinger et al 2017;Dollerup et al 2018;Martens et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One study has shown, however, that the combination increases nicotinamide adenine dinucleotide blood levels in humans. 10 Despite the paucity of evidence, the combination is being sold as a supplement that targets longevity gene activation.…”
mentioning
confidence: 99%